Mycotoxin contamination of grain of selected winter wheat genotypes - Rachoń, Leszek; Bobrzyk-Mamczarz, Aneta; Szumiło, Grzegorz (Polish Journal of Agronomy, 2016)
This study defines several mycotoxin (Aflatoxin B1, Aflatoxin B2, Aflatoxin G1, Aflatoxin G2, Ochratoxin A, De- oxynivalenol, Zearalenone, Toxin T-2, Toxin HT-2, Nivalenol, Fusarenon X, 3-Acetyl-deoxynivalenol) contamination of winter common, durum, spelt and einkorn wheat genotypes. The com- pared species (Triticum aestivum ssp. vulgare, T. durum, T. aesti- vum ssp. spelta and T. monococcum) have different susceptibility to Fusarium and toxin accumulation. Durum wheat (cv. Komnata) was the most susceptible to contamination with mycotoxins. In du- rum grain the highest level of contamination was detected, espe- cially with Deoxynivalenol (2–4 times over the allowed level for unprocessed grain). T. aestivum ssp. spelta (cv. Schwabenkorn) and T. monococcum (EN 5003) showed the lowest mycotoxin level. Triticum aestivum ssp. vulgare (cv. Tonacja) was less contami- nated with mycotoxins than Triticum durum but more than T. aes- tivum ssp. spelta and T. monococcum. Other mycotoxins in grain of the examined genotypes occurred in trace amounts.